Speech styles of Migerian and Chinese EFl learners in Malaysia / Pauline Mackenzie - Pauline, Mackenzie (2014)
This study was motivated by previous research work done on the difference in language use between males and females particularly in the style of language use. The aim of this study is to investigate the speech style of male learners from Nigeria and China. Although Malaysia is a cosmopolitan country, not many studies have been conducted to examine the speech style difference of Nigerian and Chinese learners studying in Malaysia. To conduct this study, Lakoff’s (1973; 1975) ideas concerning linguistic features in gender differences were taken into account. Particular attention is given to the usage of three linguistic features; fillers, intensifiers and affirmatives. The speaking rate of the learners was also looked at. A questionnaire was used to obtain data from 20 learners: 10 from Nigeria and 10 from China. Their speech on ‘My Family’ was recorded, transcribed and analyzed. Data were then divided into four categories; 1) fillers 2) intensifiers 3) affirmatives and 4) speaking rate. The results showed that Chinese learners use fillers at a higher rate compared to Nigerian learners, suggesting that the Chinese learners may not be as comfortable when using English. Both the Nigerian and Chinese learners used the same amount of intensifiers which shows that they do not feel passionate when talking about this topic. Nigerian learners tended to use the affirmative ‘ya’ in their speech while the Chinese learners tended to use the word ‘okay’. As for the speaking rate, it can be said that majority of the foreign learners tended to have a slower speaking rate compared to native English speakers. Consequently, the speaking rate of the Nigerians fall under the category of slow, whereas for the Chinese, the speaking rate was under the category of very slow. The findings of this research will benefit researchers working on the speech styles of foreign learners and local educators developing courses for international students coming to Malaysia.